Respuesta :
6(2x + 1) = -36 - 2x
12x + 6 = -36 - 2x
12x + 2x = -36-6
14x = -42
X = -3
12x + 6 = -36 - 2x
12x + 2x = -36-6
14x = -42
X = -3
Answer:
The value of 3x is -9
Step-by-step explanation:
Given Equation
[tex]6(2x + 1) = - 36 - 2x[/tex]
Step 1
- Distribute 6 in the expression.
[tex]12x + 6 = - 36 - 2x[/tex]
Step 2
- Combine like terms and solve the equation for x-term
[tex]12x + 2x = - 36 - 6 \\ 14x= - 42 \\ x = \frac{ - 42}{14} \longrightarrow \frac{ - 3}{1} \\ x = - 3[/tex]
But we want to know what is the value of 3x.
Step 3
- Substitute the value of -3 in 3x.
[tex]3x = 3( - 3) \\ 3x = - 9[/tex]
Hence, the value of 3x is -9
Hope this helps! If you have any questions that are related to the answer, feel free to use "Comment" feature!